Association of rs7574865 G/T polymorphism of STAT4 gene with juvenile onset of systemic lupus erythematosus - M. Yu. Krylov; M. I. Kaleda; I. A. Guseva; N. V. Konovalova; D. A. Varlamov (Современная ревматология, 2022)
Systemic lupus erythematosus (SLE) with juvenile onset (jSLE) is a complex autoimmune disease involving many organs and systems. The single nucleotide polymorphism rs7574865 of the STAT4 (signal switch and transcription activator 4) gene is associated with the risk of developing several autoimmune diseases, including SLE in adults.Objective: to verify the hypothesis of the association of the rs7574865 polymorphism of the STAT4 gene with a predisposition to jSLE. Patients and methods. In the present case-control study, the rs7574865 polymorphism was studied in 50 children with jSLE and 103 healthy control volunteers using real-time polymerase chain reaction.Results and discussion. The distribution of genotype frequencies among patients had statistically significant differences compared to controls (p=0.005). The frequencies of GG, GT, TT, GT + TT genotypes in patients with jSLE and in the control group were 36.0 and 63.1% (p=0.003); 54.0 and 33.0% (p=0.021); 10.0 and 3.9% (p=0.153); 64.0 and 36.9% respectively (p=0.003). The frequency of the mutant T allele of the studied polymorphism was higher in patients with jSLE compared with controls (37 and 20.4%, respectively; p=0.002). The association of the T allele with clinical, laboratory, and immunological phenotypes of jSLE was studied.Conclusion. The obtained data indicate the significance of the rs7574865 polymorphism of the STAT4 gene as an important risk factor for susceptibility to jSLE. An analysis of the distribution of allele frequencies between alternative groups of patients with different phenotypic manifestations of jSLE (their presence or absence) showed an association of this polymorphism with arthritis.